High infiltration of CD209+ dendritic cells and CD163+ macrophages in the peritumor area of prostate cancer is predictive of late adverse outcomes - Molina, Oscar Eduardo; LaRue, Hélène; Simonyan, David; Hovington, Hélène; Têtu, Bernard; Fradet, Vincent; Lacombe, Louis; Toren, Paul; Bergeron, Alain; Fradet, Yves (Frontiers in Immunology, 2023)
Introduction: Prostate cancer (PCa) shows considerable variation in clinical outcomes between individuals with similar diseases. The initial host-tumor interaction as assessed by detailed analysis of tumor infiltrating immune cells within the primary tumor may dictate tumor evolution and late clinical outcomes. In this study, we assessed the association between clinical outcomes and dendritic cell (DC) or macrophage (MΦ) tumor infiltration as well as with expression of genes related to their functions. Methods: Infiltration and localization of immature DC, mature DC, total MΦ and M2-type MΦ was analyzed by immunohistochemistry in 99 radical prostatectomy specimens from patients with 15.5 years median clinical follow-up using antibodies against CD209, CD83, CD68 and CD163, respectively. The density of positive cells for each marker in various tumor areas was determined. In addition, expression of immune genes associated with DC and MΦ was tested in a series of 50 radical prostatectomy specimens by Taqman Low-Density Array with similarly long follow-up. Gene expression was classified as low and high after unsupervised hierarchical clustering. Numbers and ratio of positive cells and levels of gene expression were correlated with endpoints such as biochemical recurrence (BCR), need for definitive androgen deprivation therapy (ADT) or lethal PCa using Cox regression analyses and/or Kaplan-Meier curves. Results: Positive immune cells were observed in tumor, tumor margin, and normal-like adjacent epithelium areas. CD209+ and CD163+ cells were more abundant at the tumor margin. Higher CD209+/CD83+ cell density ratio at the tumor margin was associated with higher risk of ADT and lethal PCa while higher density of CD163+ cells in the normal-like adjacent epithelium was associated with a higher risk of lethal PCa. A combination of 5 genes expressed at high levels correlated with a shorter survival without ADT and lethal PCa. Among these five genes, expression of IL12A and CD163 was correlated to each other and was associated with shorter survival without BCR and ADT/lethal PCa, respectively. Conclusion: A higher level of infiltration of CD209+ immature DC and CD163+ M2-type MΦ in the peritumor area was associated with late adverse clinical outcomes.